Análise de performance de ativos: um estudo de caso da Tesouraria do Banco do Nordeste do Brasil - Lima Filho, José Valente de (2008)
This paper has the purpose of analyzing the performance of a public financial institution’ treasury – Brazilian Northeast Bank – by the means of model of Jensen, derived from CAPM, throughout the period of January/2003 to December/2007. There were used monthly returns of the firm’s treasury portfolio and of alternative portfolios which proposed the insertion of assets that are not used by the bank yet, and applied scores to every portfolio in order to make a comparison between the treasury and alternative portfolios’ performance. There were used two proxies as free-risk rate, saving’s rate and Selic rate, and Ibovespa index was used as a market portfolio proxy. By this model, we noticed a slightly better performance for the alternative portfolios suggested.